2022
DOI: 10.1016/j.psycom.2022.100023
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical changes in pediatric in-patient admissions for mental health emergencies during the COVID-19 pandemic: March 2020 to June 2021

Abstract: COVID-19 pandemic may affect children's mental health. Children <18 years in-patiently admitted for mental health emergencies between March 2020 and June 2021 were compared to those admitted in the same period of 2018–2019 in terms of sociodemographic and clinical characteristics. There were 49 admissions in the pre-pandemic period and 60 in the pandemic period (IRR: 1.22; 95% CI: 0.84–1.79), with the latter more likely to have a family history of psychiatric disorders, a personal history of physical disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…The moderating effect of geographical region on changes in rate of emergency department visits for suicidal ideation or attempt was meta-analysed with 29 study estimates from 29 studies. 10 , 11 , 13 , 16 , 17 , 18 , 21 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 59 , 62 There was good evidence of increased rates in samples from both North America (RR 1·27, 90% CI 1·04–1·53; slight-to-moderate magnitude) 10 , 13 , 16 , 18 , 21 , 40 , 41 , 47 , 48 , 54 , 59 , 62 and Europe (1·18, 0·99–1·41; slight-to-small magnitude). 11 , 17 , 34 , 35 , 37 , 39 , 44 , 45 , 46 , 49 , 51 , 52 , 55 , 56 A single study from Australia 42 reported a moderate increase (1·59, 1·44–1·76).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderating effect of geographical region on changes in rate of emergency department visits for suicidal ideation or attempt was meta-analysed with 29 study estimates from 29 studies. 10 , 11 , 13 , 16 , 17 , 18 , 21 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 59 , 62 There was good evidence of increased rates in samples from both North America (RR 1·27, 90% CI 1·04–1·53; slight-to-moderate magnitude) 10 , 13 , 16 , 18 , 21 , 40 , 41 , 47 , 48 , 54 , 59 , 62 and Europe (1·18, 0·99–1·41; slight-to-small magnitude). 11 , 17 , 34 , 35 , 37 , 39 , 44 , 45 , 46 , 49 , 51 , 52 , 55 , 56 A single study from Australia 42 reported a moderate increase (1·59, 1·44–1·76).…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 11 , 13 , 16 , 17 , 18 , 21 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 59 , 62 There was good evidence of increased rates in samples from both North America (RR 1·27, 90% CI 1·04–1·53; slight-to-moderate magnitude) 10 , 13 , 16 , 18 , 21 , 40 , 41 , 47 , 48 , 54 , 59 , 62 and Europe (1·18, 0·99–1·41; slight-to-small magnitude). 11 , 17 , 34 , 35 , 37 , 39 , 44 , 45 , 46 , 49 , 51 , 52 , 55 , 56 A single study from Australia 42 reported a moderate increase (1·59, 1·44–1·76). Further sample-estimates representing COVID-19-related changes in suicidal ideation or attempt in New Zealand 38 (1·20, 0·44–3·25) and South Korea 50 (1·19, 0·87–1·63) had small positive observed values but had unclear magnitudes.…”
Section: Resultsmentioning
confidence: 99%
“…The national and international literature also agrees in detecting different trends of the referrals to mental Health Services according to different phases of the pandemic: a "freezing" of emergency psychiatric visits was detected during the rst pandemic period, followed by an increase in the use of emergency services and stabilization at higher levels in the following summer months [19][20][21]. It's been found out that, despite the decline in emergency departments presentations during the rst lockdown, a greater proportion of assessed children and adolescents met the admission criteria compared to the previous year, showing an increase in the acuity of mental health disorders [21,22].…”
mentioning
confidence: 79%
“…Furthermore, during the post-lockdown period, there was an increase in diagnoses of suicidal behavior ( 19 ) and, to a lesser extent, of affective ( 20 ) and anxiety disorders ( 18 ). Several factors may explain this phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…Second, children and adolescents may be particularly vulnerable to generalized stressors related to the pandemic – such as death of loved ones, family distress due to emerging economic problems, and loss of peer support networks due to lockdown measures and online schooling ( 22 , 23 ). Other authors have reported that the number of patients diagnosed with schizophrenia and eating disorders visiting the emergency department remained relatively unchanged after COVID-19 ( 19 , 20 ). Whether this is due to no increases in exacerbations of these disorders after the pandemic outbreak, exacerbations not presenting to the ED, or lack of power to detect changes in trends due to a small sample size, remains unanswered.…”
Section: Methodsmentioning
confidence: 99%